Extra : economia de energia e extensão do tempo de vida de redes ad hoc - Silva, Rone Ilídio da (2008)
This work proposes a new algorithm, called Extra, for power saving and ad hoc network life time extension. Extra is able to save power by allowing each nod to decide whether it showd be active or to changed to the sleeping state, in which the power consumption is significantly lower. The power saving is done between the nodes in order to extend the network life time, that is, extend de period of time consumed until the death of the first node. All used information can be obtained only from the routing level. Besides, Extra can be used together with any other ad hoc network reactive protocol and it is not necessary to change its features. As it is very simple, it can be used by any kind of hardware, even the most simple and not expensive ones. The simulations tests show that Extra is very effective in network power saving compared with other similar mechanisms.